Gut Microbiota-Metabolome Changes in Children With Diarrhea by Diarrheagenic E. coli - Gallardo, Pablo; Izquierdo, Mariana; Vidal, Roberto M.; Soto, Francisco; Ossa, Juan C.; Farfan, Mauricio J. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Diarrheagenic Escherichia coli (DEC) strains are a main cause of diarrhea worldwide in children under 5 years old. DEC virulence is strongly regulated by environmental conditions and metabolites produced by the gut microbiota in the intestinal tract. In this study, we evaluated changes in gut microbiota-metabolome in children with or without diarrhea produced by DEC pathotypes. Goal: To determine gut microbiota composition and metabolome in stool samples obtained from healthy children and children with diarrhea positive for DEC pathotypes. Methods: We analyzed a total of 16 age-paired stool samples: 8 diarrheal samples positive for one DEC pathotype and 8 stool samples from healthy children. To identify the microbiota composition, we sequenced the V3-V4 region of the 16S rRNA and determined operational phylogenetic units (OPU). OPU were then used to predict metabolic pathways using the PICRUSt2 software. The presence of metabolites in stool samples was determined by LC-MS. A correlation analysis was performed with the main genera from each group and main metabolites. Bacteria associated with variance of main metabolites were identified using the MIMOSA2 software. Results: DEC and healthy groups showed a statistically different microbiota composition. A decrease in Firmicutes together with an increase in Bacteroidetes and Proteobacteria was found in the DEC group compared to the healthy group. Metabolic pathway predictions based on microbiota diversity showed that pathways involved in histidine and L-ornithine metabolism were significantly different between groups. A total of 88 metabolites detected by LC-MS were included in the metabolome analysis. We found higher levels of histamine and lower levels of ornithine in DEC samples than in the healthy group. Histamine and L-ornithine were associated with a specific microbiota species and the corresponding metabolic pathways. Conclusion: Stool samples from healthy children and children positive for DEC displayed a differential metabolome and microbiota composition. A strong correlation between a gut microbiota species and certain metabolites, such as histamine and L-ornithine, was found in the DEC group. This information might be useful to identify mechanisms and signaling molecules involved in the crosstalk between microbiota and DEC pathotypes.